2022
DOI: 10.1007/s13555-022-00793-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tildrakizumab Across Different Body Weights in Moderate-to-Severe Psoriasis Over 5 Years: Pooled Analyses from the reSURFACE Pivotal Studies

Abstract: Introduction: Tildrakizumab (TIL), a monoclonal antibody that selectively targets interleukin-23p19, has been approved for the treatment of moderate-to-severe plaque psoriasis. According to the European Medicines Agency Summary of Product Characteristics, the recommended dose is 100 mg, but a 200 mg dose can be used in patients with certain characteristics, such as a high disease burden or body weight (BW) C 90 kg. Fixed one-dose biological therapies tend to become less effective in patients with high BW. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Conversely, other studies have suggested that tildrakizumab response was not modified by prior BT expossure 12,17,18 . In line with our findings, most RWE studies suggest that effectiveness was not influenced by BMI, 11–13,16 although a pooled analysis form reSURFACE 1/2 pointed to the opposite direction 22,23 . To date, RWE studies have not reported a negative impact of psoriatic arthritis history in tildrakizumab effectiveness 16,17 …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Conversely, other studies have suggested that tildrakizumab response was not modified by prior BT expossure 12,17,18 . In line with our findings, most RWE studies suggest that effectiveness was not influenced by BMI, 11–13,16 although a pooled analysis form reSURFACE 1/2 pointed to the opposite direction 22,23 . To date, RWE studies have not reported a negative impact of psoriatic arthritis history in tildrakizumab effectiveness 16,17 …”
Section: Discussionsupporting
confidence: 86%
“…12,17,18 In line with our findings, most RWE studies suggest that effectiveness was not influenced by BMI, [11][12][13]16 although a pooled analysis form re-SURFACE 1/2 pointed to the opposite direction. 22,23 To date, RWE studies have not reported a negative impact of psoriatic arthritis history in tildrakizumab effectiveness. 16,17 Though not included in the SmPC, off-label reduced dose regimens are sometimes used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no significant differences were reported in terms of PASI response rates, and adverse events up to week 244 between patients with and without metabolic syndrome, confirming tildrakizumab efficacy and favorable safety profile even in long-term follow-up also in patients with metabolic syndrome. 29 ReSURFACE studies also showed tildrakizumab as a safe treatment in moderate-to-severe psoriasis. 23,28 Indeed, tildrakizumab, at both 100 and 200 mg dosages, did not raise any safety issues in both reSURFACE trials, resulting comparable to placebo in terms of reported AEs.…”
mentioning
confidence: 94%
“…In post hoc analyses of reSURFACE 1 and reSURFACE 2 data, the long-term (5 years) safety profile of tildrakizumab was similar regardless of body weight [ 62 ] or presence of metabolic syndrome (Table 5 ) [ 63 ]. Five-year rates of AEs and AEs of interest during treatment with tildrakizumab 100 mg and 200 mg were similar between patients with psoriasis weighing < 120 kg and those weighing ≥ 120 kg [ 62 ].…”
Section: Safety Of Il-23 P19 Inhibitorsmentioning
confidence: 99%
“…In post hoc analyses of reSURFACE 1 and reSURFACE 2 data, the long-term (5 years) safety profile of tildrakizumab was similar regardless of body weight [ 62 ] or presence of metabolic syndrome (Table 5 ) [ 63 ]. Five-year rates of AEs and AEs of interest during treatment with tildrakizumab 100 mg and 200 mg were similar between patients with psoriasis weighing < 120 kg and those weighing ≥ 120 kg [ 62 ]. The combined rates (patients with events) of AEs of special interest (drug hypersensitivity, serious infections, malignancies, melanoma, NMSC, MACE, and injection site reactions) for patients without and with metabolic syndrome, respectively, were 2.1 and 2.0 for tildrakizumab 100 mg and 2.6 and 5.2 for tildrakizumab 200 mg [ 63 ].…”
Section: Safety Of Il-23 P19 Inhibitorsmentioning
confidence: 99%